Исследование условий совместимости полисахаридов Furcellaria Lamour. и Phyllophora Grev. (Phyllophora) - Микулич, Д.В. (Альгология, 2007)
Досліджено умови сумісності полісахаридів червоних водоростей Балтійського моря Furcellaria lumbricalis (Huds.) Lamour. і Phyllophora truncata (Pall.) Newroth et Taylor (Rhodophyta). Показано схожість оптичних якостей розчинів полісахаридів. Високі значення спін-спінової релаксації характерні для полісахаридних ланцюгів фурцелларана і полісахарида філлофори, що свідчить про відсутність кристалічних областей в системах цих біополімерів. Полісахариди F. lumbricalis і Ph. truncata здатні формувати однорідні стійкі композиції з високою желеподібною здатністю. Їх можна використовувати в якості структуроутворювачів – аналогів агарів і каррагенинів, а суміші фурцеллярії і філлофори – як сировину для їх отримання. Furcellaria lumbricalis (Huds.) Lamour. and Phyllophora truncata (Pall.) Newroth et Taylor. (Rhodophyta) were investigated. The resemblance of optical properties of the solutions of furcellaran and Phyllophora Grev. polysaccharides are shown. High values of spin-spin relaxation are characteristic for polysaccharide chains of furcellaran and Phyllophora polysaccharides, giving evidence of the lack of crystalline domains in the systems of these biopolymers. The polysaccharides of F. lumbricalis and Ph. truncata are able to form homogeneous and stable compositions with high gelling capacity. They may be used as structure-forming substances, agar and carrageenan analogues, and the mixture of Furcellaria and Phyllophora is a suitable raw material for their production.